2014
DOI: 10.1080/09639284.2014.905259
|View full text |Cite
|
Sign up to set email alerts
|

Self- and Peer-Assessment: Evidence from the Accounting and Finance Discipline

Abstract: Self-and peer-assessment of student work is an area that is under-researched in the accounting education literature, although the subject area of study seems to influence the results obtained in prior studies. The current study contributes to the literature by examining the accuracy and construct validity of self-and peer-assessment by accounting students. It also investigates students' views about these exercises. The findings show that whilst the self-and peer-assessment of students appear to be neither accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Interestingly, an important theme that was identified in the negative comments is that students felt that they may not accurately assess themselves, as they may be subjective during the SA process; this is consistent with existing literature (Hassan et al , 2014, p. 234). Analysis of these qualitative comments revealed that some students felt that while the SA process is beneficial, they are too critical of their own work; for example, Participant 123 noted, “I feel that it is helpful but because I am very hard on myself I make myself more negative and overwork myself on the critique that the end result are more negative than positive”.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Interestingly, an important theme that was identified in the negative comments is that students felt that they may not accurately assess themselves, as they may be subjective during the SA process; this is consistent with existing literature (Hassan et al , 2014, p. 234). Analysis of these qualitative comments revealed that some students felt that while the SA process is beneficial, they are too critical of their own work; for example, Participant 123 noted, “I feel that it is helpful but because I am very hard on myself I make myself more negative and overwork myself on the critique that the end result are more negative than positive”.…”
Section: Resultssupporting
confidence: 81%
“…Existing SA and PA literature is extensive and encompasses many disciplines (Carvalho, 2013; Dijks et al , 2018; Hassan et al , 2014, p. 226; Hill, 2016; Patton, 2012; Schmulian and Coetzee, 2019; Seifert and Feliks, 2019; Sridharan et al , 2018; Wen and Tsai, 2006; Yu, 2020). Yet, few SA and/or PA studies focus on accounting education, and these studies vary in scope (either SA or PA), purpose (to examine the accuracy, the reliability and/or the validity of the assessment) and the student task (presentations, assignments, quizzes or tests).…”
Section: Introductionmentioning
confidence: 99%
“…Although Topping () and Cho et al () indicated that peer assessment provides adequate reliability and validity in higher education, the validity of peer assessment remains inconclusive. Several studies reported that the ratings provided by peers were highly correlated with those marked by teachers (e.g., Falchikov & Goldfinch, ; Harris, ; Tsai & Liang, ; Tseng & Tsai, ), whereas inconsistent scoring between peers and teachers has also been reported (e.g., Hassan et al, ; Hovardas et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The highest figure of UZ in both items, i.e. improved teamwork abilities and having learnt from others, might be related to the abovementioned smaller class size, which encourages, on the one hand, a more personalized instructorstudent relationship and on the other hand, more interactions and strong relationships among students (Hassan, Fox & Hannah, 2014;Voynova, 2017). Finally, students consider that they played a leading role when they had been working in groups.…”
Section: Independent Variables Skills (Sk)mentioning
confidence: 96%